Upaya Meningkatkan Kinerja Mitra Binaan UKM PTPN III Nusantara Melalui Social Network dan Perceived Customer Benefit Melalui Program Kemitraan - Junaidi Junaidi; Zulkarnain Lubis; Ihsan Effendi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to determine the role of partnerships in mediating social networks and perceived value on the performance of SMEs fostered by PTPN III Nusantara. The population in this study were 785 SMEs assisted by PTPN III Nusantara which were considered successful in developing their business. The sampling technique used was accidental sampling. So that only 125 respondents were chosen by the researchers to be used as research samples. Collecting data using a questionnaire and data analysis using path analysis. The results showed that the role of this partnership was able to mediate social networks and perceived value on the performance of SMEs fostered by PTPN III Nusantara. This means that the role of partnership is indirectly able to improve the performance of the assisted SMEs at PTPN III Nusantara